1990
DOI: 10.1021/bi00454a032
|View full text |Cite
|
Sign up to set email alerts
|

Chromophore function and interaction in Escherichia coli DNA photolyase: reconstitution of the apoenzyme with pterin and/or flavin derivatives

Abstract: Native DNA photolyase, as isolated from Escherichia coli, contains a neutral flavin radical (FADH.) plus a pterin chromophore (5,10-methenyltetrahydropteroylpolyglutamate) and can be converted to its physiologically significant form by reduction of FADH. to fully reduced flavin (FADH2) with dithionite or by photoreduction. Either FADH2 or the pterin chromophore in dithionite-reduced native enzyme can function as a sensitizer in catalysis. Various enzyme forms (EFADox, EFADH., EFADH2, EPteFADox, EPteFADH., EPte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

21
184
3

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(208 citation statements)
references
References 15 publications
21
184
3
Order By: Relevance
“…The concentration of the resultant blue flavin radical (FADH ⅐ ) was estimated based on its absorbance at 580 nm (⑀ 580 ϭ 0.48 ϫ 10 4 M Ϫ1 cm Ϫ1 ) (27). Buffer Exchange-Samples were transferred into the desired buffer (usually 0.1 M NaCl, 0.05 M Tris⅐HCl, or 0.05 M HEPES (pH 6 -9.5) in 50% (v/v) glycerol) by dilution and ultrafiltration through Amicon C30 microconcentrators at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…The concentration of the resultant blue flavin radical (FADH ⅐ ) was estimated based on its absorbance at 580 nm (⑀ 580 ϭ 0.48 ϫ 10 4 M Ϫ1 cm Ϫ1 ) (27). Buffer Exchange-Samples were transferred into the desired buffer (usually 0.1 M NaCl, 0.05 M Tris⅐HCl, or 0.05 M HEPES (pH 6 -9.5) in 50% (v/v) glycerol) by dilution and ultrafiltration through Amicon C30 microconcentrators at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…Understanding why photoreactivation in Chlamydomonas relies so heavily on FO is of interest. Previous work has demonstrated that photolyase is able to bind FAD even in the absence of a second chromophore (5,39). It appears that this is also the case for PHR2p given the following two results.…”
Section: Discussionmentioning
confidence: 99%
“…The excited FADH Ϫ reversibly transfers an electron to the damaged DNA allowing the DNA to return to its original undamaged form. Although the antenna chromophore increases the repair rate of DNA photolyase 10 -100-fold under limited-light conditions, it is generally considered nonessential for photoreactivation under standard light conditions (4, 11, 12) because DNA photolyase bound to FADH Ϫ alone is sufficient to catalyze the repair of UV-induced DNA damage (5,(13)(14)(15).FO is generated from 5-amino-6-ribitylamino-2,4(1H,3H)-pyrimidinedione, an intermediate in riboflavin biosynthesis, and 4-hydroxyphenylpyruvate, a precursor to tyrosine. The reaction is catalyzed by an enzyme known as FO synthase (EC 2.5.1.77), a member of the radical S-adenosylmethionine (AdoMet) superfamily of proteins (16).…”
mentioning
confidence: 99%
See 2 more Smart Citations